The Changing Learning Needs of Saudi Student Nurses - Britiller, Myra C.; Garcia, Paul Reinald; Amponin, Aimee M. (European Scientific Journal, ESJ, 2018)
The study assessed the changing learning needs of Saudi student nurses as input to nursing curriculum. It identified the specific changing learning needs in three different domains: cognitive, affective, and psychomotor. Also, responses of faculty members to the students’ changing learning needs were determined. Relationship between the changing learning needs of students and responses of faculty members proposed inputs to nursing curriculum. The study was a descriptive cross sectional and correlational survey method. The respondents were 100 student nurses and interns, and 13 nursing faculty members of Al Ghad International Colleges for Applied Medical Sciences purposely chosen based on research criteria set by the researchers. An adapted questionnaire was used and translated its content into Arabic language. Several ways were carried out to achieve content validity before it was submitted to the research committee of the colleges and respective deans for distribution approval. A total of 100 students and 13 faculty participated in the study purposely chosen based on the criteria set by the researchers. Results were analyzed through quantitative statistics. The findings revealed that Saudi student nurses’ cognitive changing learning needs were focused on the application of student-learner approach in the classroom and educational field trips to different hospitals and health care settings. As to affective, Saudi student nurses’ topped those needs for recreational activities to build confidence and self-esteem, stress management techniques and group activities for active participation. In terms of psychomotor, the highest changing learning needs were the availability of learning materials specific to students’ needs and challenging programs outside the classroom that promotes learning. The response of faculty members based on the changing learning needs of student nurses was to attend seminars and conferences to broaden knowledge on their field of specialization to provide students with new knowledge and skills. Psychomotor domain is significant to the changing learning needs of student nurses. The study concluded that there is a need to modify and redesign the existing nursing curriculum based on the changing learning needs of student nurses. Continuing education, training and professional development of nursing faculty members is vital to meet the changing learning needs of Saudi student nurses.